Analisis Tarif Sewa Gedung Gor Flobamora Terhadap Pendapatan Asli Daerah Provinsi Nusa Tenggara Timur - Alexander Yos Patris Anggul; Nikson Tameno; Aldarine Molidya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Regional government assets are one of the pillars of revenue generation for the Regional Government. In managing regional assets, regional governments must consider various aspects ranging from needs planning, procurement, administration, utilization, maintenance and security to supervision so that regional assets are able to provide optimal contributions to the regional government concerned. Regional assets are a resource and a potential that is absolutely necessary in the administration of Regional Government, because if assets are managed well they can provide benefits to the Regional Government and the community as a source of income as well as supporting the role and function of the Regional Government as a provider of regional services to the community.